Assessment of urethral vascularity using 2D colour Doppler high-frequency endovaginal ultrasonography in women treated for symptomatic stress urinary incontinence: 1-year prospective follow-up study. Issue 1 (January 2016) - Lone, Farah; Thakar, Ranee; Wieczorek, Andrzej; Sultan, Abdul; Stankiewicz, Aleksandra
Abstract Introduction Urethral vascularity is responsible for organ perfusion. It is also believed to contribute to maintaining the normal tension in the urethral mucosa and contributes to approximately one third of urethral closure pressure. We hypothesised that in women undergoing treatment for stress urinary incontinence (SUI), there is no change in blood flow intensity. Methods In this pilot study we recruited women attending the urogynaecology clinics between July and October 2009. Exclusion criteria included symptoms of pelvic organ prolapse or urinary tract infection. Colour Doppler ultrasound was performed at the level of the mid-urethra using a high-frequency (9–12 MHz) endovaginal ultrasonography (EVUS) focusing on the following vascular parameters: flow velocity (V), area of the vessels (A), intensity of perfusion (I), Tissue Pulsatility Index (TPI) and Tissue Resistance Index (TRI). Vascular assessments were repeated at 1 year. Results We examined 67 women with symptoms of SUI (17 women had surgery and 50 conservative management, i.e., pelvic floor muscle exercises). The mean (± SD) age in the conservative and surgical groups was 46 (±11) and 40 (±9) years respectively and median (range) parity was 2 (0–8) in both groups. Compared to baseline, no statistically significant differences were observed within each group (p  > 0.05) or between the values of vascular parameters (V, A, I, TRI and TPI) at 1 year. There was also no difference in vascular parameters between the two groups. Conclusion At 12 months there is no change in vascularity parameters in women who opt for conservative or surgical treatment of SUI.